The occurrence, characteristics, and adaptation of A-to-I RNA editing in bacteria: A review - Liao, Weixue; Nie, Wenhan; Ahmad, Iftikhar; Chen, Gongyou; Zhu, Bo (Frontiers in Microbiology, 2023)
A-to-I RNA editing is a very important post-transcriptional modification or co-transcriptional modification that creates isoforms and increases the diversity of proteins. In this process, adenosine (A) in RNA molecules is hydrolyzed and deaminated into inosine (I). It is well known that ADAR (adenosine deaminase acting on RNA)-dependent A-to-I mRNA editing is widespread in animals. Next, the discovery of A-to-I mRNA editing was mediated by TadA (tRNA-specific adenosine deaminase) in Escherichia coli which is ADAR-independent event. Previously, the editing event S128P on the flagellar structural protein FliC enhanced the bacterial tolerance to oxidative stress in Xoc. In addition, the editing events T408A on the enterobactin iron receptor protein XfeA act as switches by controlling the uptake of Fe3+ in response to the concentration of iron in the environment. Even though bacteria have fewer editing events, the great majority of those that are currently preserved have adaptive benefits. Interestingly, it was found that a TadA-independent A-to-I RNA editing event T408A occurred on xfeA, indicating that there may be other new enzymes that perform a function like TadA. Here, we review recent advances in the characteristics, functions, and adaptations of editing in bacteria.